Molecular characterization of the evolution of premalignant lesions in the upper aerodigestive tract - Lechner, Axel; Kumbrink, Jörg; Walz, Christoph; Jung, Andreas; Baumeister, Philipp; Flach, Susanne (Frontiers in Oncology, 2024)
Early relapse and development of metastatic disease are some of the primary reasons for the poor prognosis of patients with head and neck squamous cell carcinoma (HNSCC). HNSCC is a heterogeneous disease which may develop in large premalignant fields of genetically altered cells. Yet knowing which individuals will progress and develop clinically significant cancers during their lifetimes remains one of the most important challenges of reducing HNSCC morbidity and mortality.To further elucidate the molecular mechanisms, we performed a focused analysis of the genome and immune microenvironment from multiple, matched normal squamous tissue, premalignant lesions, as well as primary and recurrent tumors from seven patients with p16-negative HNSCC.We performed targeted panel Next Generation Sequencing (161 genes) to analyze somatic variants from sequentially collected, matched formalin-fixed paraffin-embedded tissue (normal, premalignant, HNSCC) from two patients. These samples plus samples from five additional patients were analyzed with the Nanostring PanCancer Immune Panel. In addition, we performed shallow whole genome sequencing (0.5x coverage on average) on samples from three of these patients. Patients were, apart from one case, primarily treated with curative-intent surgery, and received subsequent adjuvant treatment, if indicated.The most frequently mutated genes were TP53 and NOTCH1. Other mutated genes included NOTCH3 and CDKN2A, among others. A significant number of mutations were private to dysplasia and invasive carcinoma, respectively, however, almost 20% were shared between them. Increasing genomic instability was observed when comparing histologically normal squamous mucosa with higher levels of dysplasia. High-grade dysplasia showed similarly rearranged genomes as invasive carcinoma. Pathways related to interferon alpha and gamma response were upregulated even in moderate dysplastic lesions with increasing expression in higher grades of dysplasia and carcinoma. SPINK5, a known tumor suppressor gene in HNSCC, was already downregulated in low-grade dysplastic lesions, indicating an early deactivation in the evolution of the disease.Genomic alterations as well as aberrant immune gene expression can be observed early in the evolution of tumors of the upper aerodigestive tract, highlighting the potential for targeting early mechanisms of disease progression.